Modeling international nuclear chemical biological defence forces in case of chemical weapons application for terrorist purposes - Inđić, Dejan R.; Rutić, Srđan Z.; Ivanković, Negovan D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Accelerated technical and technological development of civilisation during the twentieth and the beginning of the twenty-first century has fundamentally contributed to an uneven distribution of total world resources. Such distribution of resources has led to frequent armed conflicts which resulted in the use of both conventional weapons and those of mass destruction. Unlike conventional weapons, this kind of weapons possesses specific characteristics that make it very attractive for terrorist purposes. The best example for this is the terrorist attack in March 1995, when the ,,Aum Sinrikjo“ cult used sarin (toxic chemical from a lethal chemical weapons group) in the Tokio subway which resulted in 12 deaths and over 5,000 exposed to intoxication. This paper aims to present a model of using international nuclear chemical biological defence forces in case of the application of chemical weapons for terrorist purposes. Oppinions of CBRN experts were used for determining the criteria for the selection of a nuclear chemical biological defence forces model. The analytic hierarchy process (AHP) method was used to obtain optimal results. The obtained results can be used as a starting point for modeling nuclear chemical biological defence forces at international exercises with similar content.
Keywords: international forces; terrorism; CBRN units; weapons; nuclear; chemical